DAMPAK GLOBALISASI, DETERMINAN SOSIAL KESEHATAN DAN TUJUAN PEMBANGUNAN SOSIAL TERHADAP KESEHATAN GLOBAL DI INDONESIA - Langingi, Nova Lina (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2023)
Globalization is both simplifying yet a complicated health issue. It makes everything farther, faster, cheaper and deeper and serves as double edged-sword to health, as it provides extremely positive and extremely negative impacts on health in which health appointments is readily available on “click” requests, yet it makes fast food readily available, and that impacts on worsening sedentary lifestyle and other less healthy habits resulting ultimately in various health consequences to be brought into existence called “man-made diseases.” The establishment of Social Determinants on Health (SDH) and Social Developmental Goals (SDGs) needs to be reviewed in regards to the impact towards global health in the globalization perspective. This study is a narrative literature review on the impact of globalization, social determinants on health and social developmental goals on global health. The keywords are “globalization”, “social determinants on health”, “social developmental goals” and